THE FUNDAMENTAL HUMAN NEED FOR RELIGION: A PHILOSOPHICAL, PSYCHOLOGICAL, SOCIOLOGICAL, AND TRANSCENDENTAL ANALYSIS - Firiyanto Firiyanto; Zuhdiyah Zuhdiyah; Maryamah Maryamah (Jurnal Konseling Pendidikan Islam, 2026)
This article explores religion as a fundamental human need that transcends formal belief systems, encompassing philosophical, psychological, sociological, and transcendental dimensions. Employing a qualitative and analytical literature-based approach, the study examines primary and secondary sources relevant to the nature and role of religion in human life. The findings reveal that philosophically, religion provides meaning and moral direction beyond rational comprehension; psychologically, it fosters emotional balance and inner peace; sociologically, it strengthens social solidarity and interpersonal harmony; and transcendently, it connects human beings to God as the ultimate source of value and purpose. In the modern era, characterized by secularism and moral uncertainty, religion remains profoundly relevant as an ethical and spiritual compass guiding humanity toward existential balance and sustainable human flourishing.